Heterogeneity in agricultural land use decisions in Argentine Rolling Pampas : the effects on environmental and economic indicators - Cabrini, Silvina María (2019)
Argentine Pampas are one of the major regions in the world for agricultural production. There is a trend towards system simplification in this area, with soybeans being the predominant crop. One major concern of “soybeanization” is its long-term effect on productivity. There is an increasing interest in more diverse and intensive cropping sequences in order to mitigate environmental concerns related to agricultural simplification, while increasing or maintaining crop production. The aims of this study were to assess the heterogeneity of agricultural land use schemes in Pergamino, Buenos Aires, and to determine environmental and economic indicators for the different land uses. Data were collected through surveys to a sample of farmers for three cropping years. For each farm, three environmental indicators (soil organic carbon, nitrogen and phosphorus balances) and two economic indicators (crop revenue and on-farm environmental cost associated to negative soil organic carbon and nutrient balances) were computed. Under current land use and crop